Patiromer for the treatment of hyperkalemia. Issue 6 (2nd June 2020) - Colbert, Gates B.; Patel, Dhwanil; Lerma, Edgar V.
ABSTRACT: Introduction: Hyperkalemia is a chronic and life-threatening electrolyte disorder that affects millions of patients around the world with decreased kidney function, hypertension, and heart failure. Recently newer oral potassium-binding agents have been approved for clinical use, as an alternative to the decades long use of sodium polystyrene sulfonate. This review will focus on the patiromer and its use in reducing hyperkalemia. Areas covered: Pubmed was used to search from 1960 to 2020 on free subject terms: Hyperkalemia, Potassium, Patiromer, Veltassa, Kayexalate, Sodium polystyrene sulfonate, and Sodium Zirconium cyclosilicate. The authors have reviewed the literature and summarized the most salient elements in regards to patiromer. Expert opinion: Patiromer has been available on the US market since 2015 when approved by the FDA for clinical use. Clinical trials monitoring patient use for up to 1 year have shown clinically meaningful potassium reductions, sustained normokalemia, high tolerability, and without major serious adverse events. Patiromer is available to all patients experiencing hyperkalemia, no matter the disease state leading to the condition. It is likely this newer oral potassium-binding agent will help change how patients with hyperkalemia are treated in regards to sudden and chronic medical conditions.